A scientometric study of the limnological societies: inferences of research collaboration and core topics based on publication networks. Issue 3 (1st January 2016) - Kim, Ji Yoon; Joo, Gea-Jae; Kim, Hyun-Woo; Kim, Gu-Yeon; Do, Yuno
Abstract: Scientometric analysis of limnological societies and related publications revealed complex relationships among research topics and research collaborations. We applied scientometric analysis, word networks, bibliographic coupling, and author networks analysis, to 34777 publications related to limnology and monsoon research. We analyzed usage frequencies of limnology-related words in a Google corpus and found that usage frequencies of most limnological terms peaked during the 1980s. Social interest in the term "limnology" showed a gradually decreasing trend after the late 1990s. Monsoon research was focused in the Asian–Indian region but not in the European, African, and American regions. Word networks of limnological studies related to monsoons were mainly grouped into 3 clusters (Indian monsoons, East Asian monsoons, and monsoon assessment clusters). In the citation network of limnology journals, water quality, plankton, and invertebrate research groups generally showed strong internal citation networks. An author connection map of the limnological societies revealed strong modulators in the international societies, whereas research collaboration was rather limited to small groups within the entire network. This retrospective analysis will provide meaningful information to further develop and enhance international collaboration within limnological studies.